"You're going to burn some bridges if you come at it the wrong way": Reflecting on the realities of research-practice partnerships. Issue 1 (1st January 2020) - Agans, Jennifer P.; Burrow, Anthony L.; Kim, Esther S.; Garbo, Caitlin; Schroeder, Melissa; Graf, Stephanie; Davis, Tim
ABSTRACT: Collaborations between researchers and practitioners are valuable for community development but are challenging to implement. This study aimed to assess how researchers and practitioners perceive such collaborations and examine their ideas about how collaborations can be conducted more effectively. Developing one such research-practice collaboration to conduct this project, we examined the collaboration experiences of youth development researchers and 4-H practitioners in New York State. Quantitative and qualitative data from this investigation illustrate the challenges and rewards of collaboration and point to communication as a key element in success. Results also highlight the importance of researchers and practitioners having the interpersonal and practical skills to overcome considerable challenges and reveal that, although the benefit may not be equal, many on both sides are passionate about developing these partnerships. The results of this study can enable future collaborations to be more effective and useful for researchers and the communities who engage with them.